Type V Aplasia Cutis Congenita: Case Report, Review of the Literature, and Proposed Treatment Algorithm. Issue 6 (4th April 2012) - Morrow, Daniel; Schelonka, Robert; Krol, Alfons; Davies, Michael; Kuang, Anna
<x xml:space="preserve">Abstract</x> Abstract: Aplasia cutis congenita (ACC) is the congenital absence of skin. There are a number of different classifications based on distribution and associated findings. Type V ACC is unique in that the lesions are typically symmetric and found primarily on the trunk but can also include the upper and lower extremities. Type V is associated with the loss of a monozygotic co‐twin during the late first or early second trimester. Here we present an extensive case of type V ACC and a review of the literature, including a summary of treatment and outcomes. From the available literature, it appears that there is no benefit from early surgical intervention, and therefore we propose a treatment algorithm that starts with conservative management.